Fracture behavior of cracked composite plates repaired with a patch under various loading conditions - Durmus, Hatice; Kaman, Mete Onur; Yanen, Cenk; Albayrak, Mustafa (Springer India, 2025)
This study examines the mechanical behavior of patch-repaired composite plates under mixed-mode loading using the Arcan test method. The experimental study determines the effect of crack, patch length, and loading angle on the plate damage load. The energy release rates were determined by the virtual crack closure technique, and the fracture toughness of the repaired composites was calculated with finite element analysis. The study revealed that the maximum damage load of repaired plates under Mode-I loading was 5.95% higher than mixed-mode. Additionally, bearing damage occurred due to overload in the bolt holes caused by the high strength.
Keywords: Carbon fiber composite; mixed-mode fracture; patch; repair; arcan